Surrender : how the Clinton administration completed the Reagan revolution - Meeropol, Michael (The University of Michigan Press, 2000)
In Surrender, Michael Meeropol takes a close look at what actually happened to the American economy during the years of the "Reagan Revolution," revealing with compelling evidence the policies that were truly responsible for the failure to generate rapid growth and other economic improvements.